Effect of palm oil subsidies on productivity and well-being of independent smallholders - Norlida Hanim Mohd Salleh,; Liu Jingjing,; Nurul Atiqah Mohd Suib,; Khairuman Hashim,; Md Shafiin Shukor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to investigate the impact of subsidies on productivity and the subsequent effect of productivity on the well-being of oil palm independent smallholders (ISH). It specifically analyses the impact of palm oil subsides on productivity and the well-being of ISH based on the soil types of the palm oil plantation. A semi-structured interview method was used, and 475 questionnaires were validated for data analysis. The Principal Component Analysis (EFA) and Structural Equation Modelling (SEM) were used for data analysis. The well-being index was measured through eight components, namely income and wealth, employment and income, residential conditions, work-life balance, education and skill level, environmental quality, and subjective well-being. The results show that the well-being of independent smallholders whose plantations are based on peat and alluvial soil is higher than those with mineral soils. The findings further show that subsidies are expected to improve the productivity of the smallholders that have plantations with mineral soils, which in turn enhance their well-being. This study extends the existing literature on the well-being of independent smallholders by introducing a well-being index. In improving the productivity of smallholders that ultimately contribute to their well-being, the provision of subsidies should be continued in a targeted manner by the government through agencies such as Malaysian Palm Oil Board.